Critical Thinking Education in Visual Communication Design in China: Current Status and Key Challenges - Wu, Xiaoyi; Lee, Seungjin (Journal of Educational Research and Policies, 2025)
This study explores the current status and challenges of integrating critical thinking education into visual communication design programs in Chinese universities. It analyzes three key dimensions: policy direction, instructional practice, and implementation constraints. Although national policies emphasize innovation and critical thinking, the study finds that these goals are insufficiently realized in practice due to teacher-centered pedagogies, rigid curricula, and limited faculty preparedness. Drawing on international models from institutions such as Parsons School of Design and the Royal College of Art, the paper highlights global strategies that embed critical inquiry into seminars, interdisciplinary projects, and reflective assessment. It also examines emerging domestic practices in China, including AI-assisted coursework and project-based collaboration, which demonstrate initial success but remain uneven across institutions. The study argues that critical thinking should be a core component of design education, not an ancillary objective. Systemic alignment across curriculum design, teacher training, and assessment frameworks is essential to foster analytical, creative, and socially responsible design professionals. This research offers theoretical insight and practical recommendations for advancing critical thinking education within China’s evolving design education landscape.